Clinical researchVariability in the response to dexamethasone treatment in term neonates with respiratory failure - Attar, Mohammad; Becker, Michael A.; Dechert, Ronald E.; Donn, Steven M. (Archives of Medical Science, 2009)
Introduction: We aimed to evaluate the effect of a short course of dexamethasone on pulmonary function and mechanics in term newborn infants with respiratory failure utilizing patient monitoring devices. Material and methods: We conducted a retrospective review of term newborn infants, supported with conventional mechanical ventilation, and treated with pressors and short courses of dexamethasone (Ł 48 h) within the first week of life. Using a quasi-experimental design, where each patient served as his own control, we evaluated changes following the first dose of dexamethasone. We analyzed data from 36 newborn infants (gestational ages 39 ±0.6 weeks, birth weight 3.6 ±0.6 kg, oxygenation index 15 ±10). The first dexamethasone dose was given at 23 (17-30, median; IQR) h. Results: Significant improvements in pulmonary function and mechanics and a significant decrease in the doses of pressors used were noted 12 h after the first dexamethasone dose. These improvements were sustained for the duration of data analysis. A subgroup of newborn infants subsequently treated with inhaled nitric oxide (iNO subgroup) had slower improvement in their oxygenation and ventilation than newborn infants who did not need iNO (CMV subgroup). The two subgroups had similar changes in mean arterial pressure and doses of pressors at the analyzed time points following the first dexamethasone dose. Conclusions: Improvement in lung function and mechanics and a decrease in doses of pressors could be detected within 12 h of initiation of dexamethasone therapy. Changes observed in this study can be useful in designing future randomized controlled trials.